Linz Café : Valutazioni dell'autore - Alexander, Christopher
El arquitecto desarrolla la idea y análisis de la obra.
Keywords: ALEXANDER ,CHRISTOPHER; TEORIA; TEORIA PROYECTUAL; AUSTRIA; LINZ; CAFETERIAS